Impact of land cover change on water regulation services in the Ratuwa River Basin, Churia Region, Nepal - Kandel, Sita Ram; Taweepreda, Wirach; Techato, Kuaanan; Ghimire, Hari Prasad; Joshi, Hari Prashad (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of land cover change on water regulation services in the Ratuwa River Basin, Churia Region, Nepal, over 30 years (1990–2020), with the aim of quantifying land cover transitions and their hydrological and economic implications. Multi-temporal Landsat and Sentinel-2 imagery were analyzed to detect changes in forest, wetland, and agricultural areas. The Soil and Water Assessment Tool (SWAT) was applied to simulate hydrological processes, while benefit-transfer methods were used to economically value water regulation services, including flood mitigation, groundwater recharge, and water purification. Forest cover declined by 35% and wetlands by 20%, while agricultural land increased by 25%. These changes resulted in a 40% increase in surface runoff, a 30% reduction in groundwater recharge, and a 50% rise in flood frequency. The economic valuation indicated a 25% overall decline in water regulation service value. Land cover transformations have significantly degraded the basin’s capacity to regulate water, with direct consequences for ecological stability and socio-economic resilience. Restoration of forests and wetlands, promotion of sustainable agricultural practices, and integrated watershed management are critical to enhancing water regulation functions and mitigating climate-related risks in the Ratuwa River Basin. The findings provide evidence-based guidance for policymakers, watershed managers, and conservation practitioners to design targeted interventions for sustainable ecosystem service management.